Evaluation of decalcification for recovery of DNA from bone. (December 2017) - Iyavoo, S.; Hadi, S.; Goodwin, W.
Abstract: The effect of decalcification on pulverised bone samples was studied to evaluate its value when processing reasonably good quality samples. The decalcified and non-decalcified bone samples were extracted using phenol-chloroform extraction method, quantitated with GoTaq ® qPCR Master Mix (Promega ®, UK) using Applied Biosystems ® 7500 Real-Time PCR System (Thermo Fisher Scientific ®, UK) and amplified using an in-house amplification multiplex. The results showed that the decalcification of bone samples is not a necessary when processing good quality samples and higher DNA yields were obtained without the decalcification process. The electropherograms produced from the extracted DNA samples without decalcification were good quality and displayed no PCR inhibition.